Tinjauan Yuridis Pinjaman Online Dalam Layanan Financial Technology di Indonesia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Peer to peer lending or online loans are online money lending services commonly known as financial technology, which currently generally take the form of applications. Online loans really help people who need fast and easy funds for both consumptive and productive purposes. This service is increasingly mushrooming in Indonesia due to interest from the community itself, resulting in the emergence of illegal online loan apllications which have a detrimental impact on consumers. The normative juridical method used in this research is conducting a literature study on secondary data. The research results show legal protection and the level of effectiveness of supervision for consumers who are harmed by illegal online loan applications.